Relações interculturais em processo educativos de povos ribeirinhos da Amazônia - COSTA, Kleby Miranda (Universidade Federal do Pará, 2020)
Intercultural practice, in the teaching of foreign languages, contributes to the construction of soothing relationships in the field of tolerance, respect for others and the reception of a positive reading of the social and cultural plurality that envisions the educational life of students. The objective of this work was to analyze the intercultural translations in the practice of foreign language teachers, at the Almirante Barroso Elementary School, in the city of Mocajuba PA, highlighting in this process the cultural translation and the linguistic dimension in the riverside school. During this investigative journey, this project presented theoretical contributions that helped to form a new vision in these between places of linguistic and cultural interaction: Jorge Larrosa (2002); Jacques Derrida (2002) in a postcolonial view stood out: Homi Bhabha (2011) and with a post-critical approach in the field of curriculum: Sandra Corazza (2007); Michael Foucalt (2013) and Tomaz Tadeu da Silva (2000). The results pointed out that the linguistic elements are directly linked with the cultural questions of the language being studied, as well as of the local culture itself. This connection occurs through a dialogue between identity and difference. This study aimed at creating a social project in 2014 that partnered with public universities in the region, where it provided free English language classes to several young people from public schools in the city of Mocajuba PA.